Exploring the postsecular : the religious, the political and the urban - Molendijk, Arie L.; Beaumont, Justin; Jedan, Christoph (Leiden ; Boston : Brill, 2010)
The re-emergence of the religious in secular domains has led prominent scholars such as Jrgen Habermas and Charles Taylor to speculate about a new postsecular age. The alleged shift from the secular to the postsecular is most visible in the spheres of urban public space, governance and civil society. This volume addresses contemporary relations between religion, politics and urban societies primarily from a theoretical perspective, while also paying attention to empirical manifestations of the central conceptual ideas. The primary focus is the relations between public religion, deprivatization.
Preface; List of Contributors; Part One Exploring the Field: Introductory Essays; Transcending the Particular in Postsecular Cities; Cutting through the Postsecular City: A Spatial Interrogation; Part Two Conceptualizing the Postsecular; Spaces of Postsecularism; Contrasting Modernities: 'Postsecular' Europe and Enspirited Latin America; How Ethnocentric is the Concept of the Postsecular?; The Transformation of Religious Culture within Modern Societies: From Secularization to Postsecularism.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Religion and sociology; Cities and towns -- Religious aspects; SOCIAL SCIENCE -- Sociology of Religion; Cities and towns -- Religious aspects; Religion and sociology; Electronic books